2021
DOI: 10.3892/mmr.2021.12047
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane inhibits cell proliferation and migration of glioma by targeting the miR‑27b/VEGF axis

Abstract: Poor prognosis in patients with glioma is primarily due to rapid tumor growth and cell invasion and migration. In addition, microRNA (miR)-27b is decreased in metastatic glioma. The present study investigated whether sevoflurane inhibited glioma cell progression by targeting miR-27b. Cell proliferation was analyzed using a Cell Counting Kit-8 assay and a wound healing assay was used to detect cell migration. Western blotting and reverse transcription-quantitative PCR analysis were performed to determine the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For example, Zeng et al (2020) confirmed that miR‐150‐5p could affect the migration and angiogenic ability of extravillous trophoblast cells by regulating the expression of VEGF and MMP9. In addition, Zhan et al (2021) confirmed that VEGF expression was down‐regulated and MMP2 and MMP9 levels were inhibited in SEV‐treated glioma cells. Our results were consistent with these findings, which revealed that the MMP2, MMP9, and VEGFA levels were significantly down‐regulated in OSCC cells treated with 3.4% and 5.1% SEV, confirming that SEV inhibited OSCC cell migration, invasion, and angiogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Zeng et al (2020) confirmed that miR‐150‐5p could affect the migration and angiogenic ability of extravillous trophoblast cells by regulating the expression of VEGF and MMP9. In addition, Zhan et al (2021) confirmed that VEGF expression was down‐regulated and MMP2 and MMP9 levels were inhibited in SEV‐treated glioma cells. Our results were consistent with these findings, which revealed that the MMP2, MMP9, and VEGFA levels were significantly down‐regulated in OSCC cells treated with 3.4% and 5.1% SEV, confirming that SEV inhibited OSCC cell migration, invasion, and angiogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…SCC4 and HSC3 cells were treated with SEV according to the previous method (Zhan et al, 2021). Briefly, SCC4 and HSC3 cells (1 × 10 5 cells/well) were inoculated into six-well plates and routinely cultured overnight in DMEM medium.…”
Section: Sev Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that CHROMR can act as a sponge for various miRNAs (Hennessy et al, 2019;Wang et al, 2022), but it would be difficult to attribute miRNA sponging to observed effects on glioma. For example, miR-27b, which CHROMR seems to be able to sponge (Hennessy et al, 2019) has both been linked with glioma progression (Chen et al, 2011;Liu et al, 2015;Miao et al, 2020) and glioma Frontiers in Molecular Biosciences frontiersin.org repression (Chang et al, 2020;ZHAN et al, 2021). Therefore, alternate means of PRKRA-CHROMR interaction are possible, but further experiments would need to be done to elucidate the mechanism.…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 99%
“…46 Also, sevoflurane promotes the apoptosis of laryngeal squamous cell carcinoma in-vitro and inhibits its malignant progression via miR-26a/FOXO1 axis. 47 In a large number of glioma studies, sevoflurane has shown anti-tumor effects through multiple miRNA pathways, For example, increasing the expression of miR-637, 48 miR-124-3p, 49 miR-34a-5p, 50 miR-146b-5p, 28 miR-210, 51 miR-27b, 52 or miR-144-3p 53 to regulate its corresponding downstream molecules and inhibit the migration and invasion of glioma cells. In addition to directly acting on miRNA, sevoflurane can play a regulatory role by acting on upstream circRNA.…”
Section: Inhalation Anesthesia and Gene Expressionmentioning
confidence: 99%